Effect of the Dust on the Performance of Solar Water Collectors in Iraq - Omer Khalil Ahmed (International Journal of Renewable Energy Development, 2016)
There is little research about it in present literatures in Iraq. So the effect of dust accumulation on the performance of conventional of solar collectors is analyzed. The experimental study was carried out mainly on a flat solar collector, which comprised the major part of this work. According to the experimental results obtained, there is a limited decrease in the instantaneous efficiency which was 1.6 % for the dirty collector. At load condition, the outlet temperature reaches a maximum value of 43.85oC at 12 noon without dust on the front glass and 33.7 oC in the presence of the dust. The instantaneous efficiency reaches its maximum value of 49.74 % at 12 noon without dust and 48.94% with dust after that the efficiency was decreased. The variation of useful transferred energy closely follows the variation of solar intensity and reaches its maximum value of 690 W/m2 at 12 noon in the presence of the dust for this particular day. It is also observed that, at the second half of the day, there is a large decrease in the instantaneous efficiency resulting from a large reduction in the useful energy transferred. Therefore, for Iraqi places, daily cleaning of the glass covers is strictly recommended as part of the maintenance works but the equipment should be cleaned immediately after a dust storm to keep the collector efficient. Article History: Received August 16, 2015; Received in revised form Nov 17, 2015; Accepted Dec 19, 2015; Available onlineHow to Cite This Article: Ahmed, O.K (2016). Effect of the Dust on the Performance of Solar Water Collectors in Iraq. Int. Journal of Renewable Energy Development, 5(1), 65-72.http://dx.doi.org/10.14710/ijred.5.1.65-72